O Frankenstein ou o Prometeu moderno existencialista: uma análise da condição humana da criatura de Frankenstein pela perspectiva sartriana - Moura, Mellyssa Coêlho de (2021)
The proposed research analyzes the construction of the human condition through the character referred to as “the creature” in Mary Wollstonecraft Shelley's novel Frankenstein or the modern Prometheus (1818), using Jean-Paul Sartre's existentialist perspective. This study hypothesizes that the creature's relentless search for self-knowledge and understanding of existence and freedom can be interpreted as an existential conflict he experiences. This analysis reveals that the feelings of abandonment, anguish, and despair vividly described by the creature are essential for his process of self-creation in a world where his existence was imposed upon him. Sartre's philosophy, articulated in Existentialism is a humanism (1987) and Being and nothingness (2013), provides a framework for understanding the character's journey toward self-creation and how he perceives his freedom within this process. Ultimately, this perspective aids in comprehending the existential reflection employed by Mar W. Shelley as a critical element in constructing the creature's identity. By rethinking the human being who defines their essence through choices and actions, we can see that Mary W. Shelley's creature symbolizes the human condition of individuals who, like him, have their existence imposed upon them yet strive to exist in freedom.